Analisis Motivasi Kerja Generasi Z Yang Dipengaruhi Oleh Lingkungan Kerja dan Komitmen Kerja - Yuli Fajriyanti; Asmadhini Handayani Rahmah; Sofia Ulfa Eka Hadiyanti (Journal of Trends Economics and Accounting Research, 2023)
This research aims to examine the influence of work environment and work commitment on the work motivation of Generation Z employees in Samarinda City. This study employs a quantitative approach with the population being all Generation Z individuals in Samarinda City. The sample consists of 141 respondents obtained through purposive sampling technique. Data collection is conducted using a questionnaire distributed through Google Form using the Likert scale. The analysis technique used is multiple linear regression through the SPSS software. The results of this study indicate that partially, the t-test results show that the work environment (x1) has a significance value of 0.002 ≤ 0.10, which means that the work environment significantly influences the work motivation of Generation Z. The t-test results for work commitment (x2) on work motivation (y) have a significance value of 0.006 ≤ 0.10, indicating that work commitment significantly affects the work motivation of Generation Z. Moreover, simultaneously, the F-test results for both the work environment (x1)and work commitment (x2) on work motivation (y) have a significance value of 0.001 ≤ 0.10, signifying that the work environment and work commitment, when considered together, significantly influence the work motivation of Generation Z.